Structural levels of rhythm and form in African music: with particular reference to the West Coast - Ekwueme, Lazarus (International Library of African Music, 1975)
The theories propounded by Heinrich Schenker, the great early 20th Century German theorist, as enunciated in several treatises culminating in Der Freie Satz, 1935, have aroused enormous controversy among music theorists. We are awáre that some of our readers may not be familiar with the works and theories of Schenker. Since many of Schenker's works are still not available in translation, we gladly refer interested readers to some of Schenker's theories available in the works of other theorists,1 including notably: Katz (1935), Sessions (1935), Mann (1949), Jonas (1954), Forte (1959), Salzer (1962), Beach (1969), Komar (1971), and Rothgeb (1972), among others. In spite of the controversy which surrounds Schenker's theories, even those who are not at all in sympathy with his ideas tend to accept, even if reservedly, the principle of the existence of the three structural levels in all tonal music. It is fair then to say that there is a measure of agreement in regard to structural levels in music
Keywords: African Music